Molecular characterization of candidate gene for pungency in Capsicum spp. - Anju Viswanath (Centre for Plant Biotechnology and Molecular Biology, College of Horticulture, 2016)
Chilli, also known as “Wonder spice”, has been cultivated since 3000 BC. Out of the 21 identified species of chilli, C. annuum, C. chinense, C. frutescens, C. baccatum and C. pubescens are the domesticated species. It is a major vegetable cum spice crop which can impart pungency, colour and aroma to the human foods. Pungency is one of the most important and peculiar character of all the species belonging to the genus Capsicum. Capsaicinoids are the alkaloid compounds which are responsible for pungency in chilli. Because of the nutraceutical properties possessed by these capsaicinoids, it has much importance in manufacturing several drugs. Though so many studies are conducted to understand the genetic mechanisms behind pungency, the gene action responsible for its production is still an enigma. This experiment was undertaken with the objective to assess the molecular mechanisms behind different levels of pungency in different species of Capsicum. The investigations were carried out in ten chilli genotypes namely, Ujwala, Anugraha, Byadagi Dabbi, Byadagi Kaddi, paprika Kt-Pl-19 and bell peppers Arka Gaurav and Arka Mohini (C. annuum), Vellayani Thejus (C. chinense) and White Khandari, Vellayani Samrudhi (C. frutescence). Among the genotypes Anugraha, Ujwala, Vellayani Thejus, Vellayani Samrudhi and White Kandari are pungent lines and Kt-Pl-19, Byadagi Dabbi, Byadagi Kaddi, Arka Mohini and Arka Gaurav are non-pungent lines. Good quality genomic DNA has been extracted from all the genotypes with an absorbance ratio ranging from 1.79 - 1.85 and concentration more than 1000 ng/μl. The DNA was screened with five pungency specific SCAR (Sequence Characterized Amplified Region) primers. Among the five SCAR primers used, three were specific for Pun1 locus (MAP1F/R, Pun1 1 fwd1/rev, Pun1 3 fwd/rev1) and two were specific for CS (Capsaicinoid synthetase) gene (CSF1/R2, BF7/R9). Pun1 and CS are the loci responsible for the synthesis of putative acyl- transferase and capsaicin synthase enzymes leading to the synthesis of capsaicinoids. The results revealed that MAP1F/R is the most significant primer which gave distinct amplifications in both pungent lines and non-pungent lines. A 15 bp deletion was clearly identified in the non-pungent lines compared to the pungent lines. This resultii revealed that the 15 bp deletion in the non-pungent lines is the reason for the absence of pungeny in them. The other two primers Pun1 1 fwd1/rev, Pun1 3 fwd/rev1 gave amplification only for pungent lines in C. annuum and C. frutescence respectively since Pun1 1 and Pun1 3 are the mutant alleles of Pun1 locus present in the respective species. The capsaicin, which is a capsaicinoid compound contributing about 69 per cent of pungency, is produced with the help of the capsaicin synthase enzyme produced from the CS gene. The primers specific for the CS gene have amplified only in the pungent lines. This result revealed that the nucleotide change in the primer binding region is the reason for the absence of pungency in them. The amplicon sequences of CS gene was subjected to insilico analysis such as BLASTn and Clustal Omega, which identified that the CS gene whose location was not yet confirmed also resides within the Pun1 locus. The insilico analysis has also proven that the 15 bp deletion identified in the non-pungent lines were located at the ORF3 in the Pun1 locus. This deletion in the coding region significantly affects the capsaicinoid formation for the pungency. Irrespective of the species, the deletions occurring in the coding regions of the Pun1 locus and CS gene, are the reasons for the variation of pungency levels in chillies. All the five primers attempted were promising and can be utilized to distinguish the pungent and non-pungent lines even in the seedling stage and hence in marker assisted selection (MAS). Identification of the location of CS gene inside the Pun1 locus is the most striking finding of this study. From this it can be infered that Pun1 locus, which is in the chromosome 2 of chilli is the major deciding locus for the production of capsaicinoids.